2016
DOI: 10.1016/j.bbamem.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel activity of the CSFV p7 viroporin in surrogates of the ER lipid bilayer

Abstract: Viroporins comprise a family of non-structural proteins that play significant and diverse roles during the replication cycle of many animal viruses. Consequently, they have become promising targets for inhibitory drug and vaccine development. Structure–function traits common to all members of the family are their small size (ca. 60–120 aa), high hydrophobicity, and the presence of helical domains that transverse the membrane and assemble into oligomeric-permeating structures therein. The possibility that virop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 49 publications
5
24
0
Order By: Relevance
“…Additionally, we found that the cytoplasm Ca 2+ was reduced by approximately 23% after viral incubation, which was similar to the cell after treatment with TG, suggesting that the decrease in cytoplasm Ca 2+ may contribute to IRE1 activation. However, on the contrary, cytoplasm Ca 2+ was up-regulated (approximately 20%) at 24 h post infection (data not shown), this comes as no surprise because CSFV P7 act as a viroporin that modify membrane permeability, in turn leading to Ca 2+ influx ( Aguilella et al, 2016 ; Largo et al, 2016 ). This make us question which structural protein of CSFV is involved in cytoplasm Ca 2+ reductions during or soon after virion entry may contribute to IRE1 activation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, we found that the cytoplasm Ca 2+ was reduced by approximately 23% after viral incubation, which was similar to the cell after treatment with TG, suggesting that the decrease in cytoplasm Ca 2+ may contribute to IRE1 activation. However, on the contrary, cytoplasm Ca 2+ was up-regulated (approximately 20%) at 24 h post infection (data not shown), this comes as no surprise because CSFV P7 act as a viroporin that modify membrane permeability, in turn leading to Ca 2+ influx ( Aguilella et al, 2016 ; Largo et al, 2016 ). This make us question which structural protein of CSFV is involved in cytoplasm Ca 2+ reductions during or soon after virion entry may contribute to IRE1 activation.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it is not surprising that many viruses have evolved different strategies to customize or manipulate the UPR program for their own benefit ( He, 2006 ; Ambrose and Mackenzie, 2011 ; Lyoo et al, 2015 ). Thus far, a number of documents have reported that the CSFV life cycle was associated with ER ( Tang et al, 2010 ; Guo et al, 2011 ; Gladue et al, 2014 ; Aguilella et al, 2016 ; Largo et al, 2016 ). Nevertheless, the significance and associated mechanisms of UPR in CSFV infection remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal micrographs depicted in Fig. 3A compare untreated ER-GUVs (negative control) with those treated with the pore domain of classical swine fever virus viroporin p7 (p7C) (positive control) (11) or the different FMDV 2B peptides. Negative-control vesicles and those treated with the 2B1(28 -56) or 2B3(79 -106) peptide were viewed as dark (empty) spheres surrounded by the orange-labeled lipid bilayer, against a green background containing the permeant Alexa Fluor 488 dye.…”
Section: Resultsmentioning
confidence: 99%
“…CSFV nonstructural protein p7 has been previously shown to be a virally encoded pore forming protein, or viroporin, which is essential for virus replication as well as for virulence in swine [ 4 ]. p7 has also been further characterized in terms of the protein domains and critical residues involved in pore forming activities [ 5 , 6 , 7 ]. However, little is known about other functions of p7 or the possible interaction of p7 with the host proteins during virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also demonstrated that pore formation in our ER modeled membranes by the p7 C-terminal domain depends on two sequence determinants of the protein: the C-terminal transmembrane helix (comprised by residues 39–67), and the preceding polar loop (residues 33–38), which regulates the pore forming activity [ 5 ]. In addition, we showed that p7 actually induces two types of pores with slightly different sizes and opposite ion selectivity [ 6 ]. Specific amino acid substitutions affecting conserved residues within these areas of the protein severely affect ER-like membrane permeabilization [ 7 ].…”
Section: Introductionmentioning
confidence: 99%